Sejarah Kerajaan Amanatun Pada Masa Pemerintahan Raja Abraham Zacharias Banunaek Tahun 1920-1946 - Nomleni, Defifi Sarlin; Ndoen, Fransina A; Wisnuwardana, I Gede W (Universitas Nusa Cendana, 2024)
The objectives of this study are: (1) to determine the role of King Abraham Zacharias Banunaek in the Kingdom of Amanatun from 1920 to 1946; (2) to determine the process of government administration in the Kingdom of Amanatun from 1920 to 1946. Historical method. The results of the study are: (1) The role of the king in the political, social, and economic fields. As the head of government/autonomous region, he was given the authority by the government to designate conservation areas in his territory as nature reserves or wildlife refuges with the approval of the Resident or Governor in accordance with the legal system. (2) The process of government administration in the Amanatun kingdom during the reign of King Abraham Zacharias Banunaek. In carrying out his administration, the King was assisted by the Bana, Nokas, Liunokas, Kobi, Benu, Tahun, Nenabu, and Missa tribes.